2010
DOI: 10.1089/pho.2009.2587
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laser (λ670 nm) and Dexamethasone on the Chronology of Cutaneous Repair

Abstract: Laser was effective in reducing swelling and polymorphonuclear cells and accelerated tissue repair, even in the presence of dexamethasone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Despite the increase in density of collagen fibers observed in the group of three laser applications, the difference was not significant compared to the control group of six and 10 and the irradiated group that received six applications, suggesting no formation of new collagen fibers in the intact skin. However, laser action in the treatment of tendons [28] and on skin wound healing therapy increased collagen fibers [5, 8, 17, 29, 30]. The difference between these results and those of our study may be explained by irradiation having been applied on intact skin of our animals, which have no need of a major renovation of collagen.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Despite the increase in density of collagen fibers observed in the group of three laser applications, the difference was not significant compared to the control group of six and 10 and the irradiated group that received six applications, suggesting no formation of new collagen fibers in the intact skin. However, laser action in the treatment of tendons [28] and on skin wound healing therapy increased collagen fibers [5, 8, 17, 29, 30]. The difference between these results and those of our study may be explained by irradiation having been applied on intact skin of our animals, which have no need of a major renovation of collagen.…”
Section: Discussioncontrasting
confidence: 67%
“…Dermatological researches have also reported experimental improvements associated with LLLT for facial rejuvenation treatment [4] and cutaneous wound healing [5]. However, as presented in the literature, different laser types, energy density, duration of treatment, and other parameters were used in the studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dexamethasone is a well-known drug due to its capacity to stimulate proliferation of mesenchymal stem cells, 30 and because of its anti-inflammatory properties. 7 Dexamethasone has been used to treat cancer, 42 skin diseases, 43 acute bacterial meningitis, 44 and other diseases. Also, dexamethasone can be used for local anesthetic pain relief therapy; 45 however, skin atrophy is accelerated by topical dexamethasone treatments, which is widely used in dermatology.…”
Section: Adhesion and Proliferation Testmentioning
confidence: 99%
“…Some physical agents have been used to treat the skeletal muscle conditions, including low-laser therapy (LLLT) (Mesquita-Ferrari et al 2011;Baptista et al 2011). This therapy is effective in reducing post-injury inflammatory processes, stimulating the formation of new blood vessels and accelerating soft tissue healing (Chung et al 2010;Marchionni et al 2011). Some studies have demonstrated that LLLT has stimulatory effects on muscle cells and skeletal muscle regeneration after an injury (Amaral et al 2001;Baptista et al 2011).…”
Section: Introductionmentioning
confidence: 99%